2009
DOI: 10.1103/physrevb.79.020502
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity without diamagnetism in systems with broken time-reversal symmetry

Abstract: We analyze the phase diagram of superconductors with a broken time-reversal symmetry in an external magnetic field. Ferromagnetism ͑broken time-reversal symmetry͒ originates either from the electron spin or the intrinsic angular momentum of Cooper pairs ͑chiral p-wave superconductors such as Sr 2 RuO 4 ͒. In addition to the Meissner and the mixed states, the phase diagram includes also the cryptoferromagnetic state with intrinsic domain structure independent of sample shape and size. The cryptoferromagnetic st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Detailed theoretical calculations have suggested that Sr 2 RuO 4 is close to a ferromagnetic (FM) instability [6,7] with strong FM spin fluctuations which may lead to spin triplet p-wave superconductivity [8]. In spite of the extensive studies carried out over the past decade, the multifaceted properties of this material, with many open questions, continue to attract considerable attention, both experimental and theoretical [9][10][11]. One of the highly debated questions is the structural instability in Sr 2 RuO 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Detailed theoretical calculations have suggested that Sr 2 RuO 4 is close to a ferromagnetic (FM) instability [6,7] with strong FM spin fluctuations which may lead to spin triplet p-wave superconductivity [8]. In spite of the extensive studies carried out over the past decade, the multifaceted properties of this material, with many open questions, continue to attract considerable attention, both experimental and theoretical [9][10][11]. One of the highly debated questions is the structural instability in Sr 2 RuO 4 .…”
Section: Introductionmentioning
confidence: 99%
“…While the DWs in various realizations of the chiral p-wave state have been extensively studied [6][7][8][9][10][11][12][13][14][15][16], their dynamic properties have received comparatively little theoretical attention, despite the evidence of the DW motion in Sr 2 RuO 4 [4,17]. In this letter, we microscopically calculate the friction coefficient and effective mass of a moving DW.…”
mentioning
confidence: 99%